Impact of GB virus C viraemia on clinical outcome in HIV‐1‐infected patients: a 20‐year follow‐up study. Issue 4 (7th October 2013) - Ernst, D; Greer, M; Akmatova, R; Pischke, S; Wedemeyer, H; Heiken, H; Tillmann, HL; Schmidt, RE; Stoll, M
<x xml:space="preserve">Abstract</x> Objectives The impact of coexisting GB virus C (GBV‐C) infection on the clinical course of HIV infection remains controversial. Early data from HIV‐1 infected patients attending the Hannover Medical School in 2001 suggested prognostic benefit in GBV‐C viraemic patients. The aim of this study was to evaluate patterns in long‐term mortality and morbidity outcomes in this cohort. The impact of the introduction of antiretroviral therapy (ART) on the perceived benefits of GBV‐C viraemia was subsequently investigated. Methods A retrospective follow‐up analysis of data in this cohort was performed. GBV‐C status (GBV‐C RNA positive, antibodies against GBV‐C envelope protein E2 or no evidence of GBV‐C exposure) had been determined at enrolment, with several markers of HIV disease progression (such as viral load and CD4 cell count) being collated from 1993/1994, 2000 and 2012. These eras were chosen to reflect variations in treatment strategies within the cohort. In addition, mortality and HIV‐related morbidity data were collated for all patients. Results Complete data were available for 156 of 197 patients (79%). In highly active antiretroviral therapy (HAART)‐naïve patients, GBV‐C RNA positivity conferred significant improvements in the course of HIV infection and mortality as well as lower rates of HIV‐related diseases. E2 positivity alone conferred no significant advantage. With the advent of HAART, however, the benefits GBV‐C RNA positivity disappeared. Conclusions Although GBV‐C coinfection appears to inherently improve morbidity and mortality in HIV‐infected patients, modern HAART has eradicated these advantages. Evidence of synergy between GBV‐C status and HAART response exists, with further studies examining the role of GBV‐C in existing treatment de‐escalation strategies being required.